The Effect of E-Service Quality, Website Design, E-Trust, and Perceived Risk on E-Satisfaction: Survey of Shopee User Students in Sleman and Yogyakarta City - Oktariani, Theresia Omiwa; Wisnalmawati, Wisnalmawati; Darpito, Surpiko Hapsoro (Jurnal Ilmiah Manajemen Kesatuan, 2022)
The purpose of this study was to determine the effect of e-service quality, website design, e-trust, and perceived risk on e-satisfaction (a survey of Shopee user students in Sleman and Yogyakarta City). This type of research is survey research using a questionnaire. The population in this study were all of the Shopee user students in Sleman and Yogyakarta City. This study used a sampling technique in the form of purposive sampling with 100 respondents who are students who live in Sleman and Yogyakarta City and have made purchases at Shopee at least two times as samples. The data analysis technique used in this study is multiple linear regression analysis with hypothesis testing, namely the F test and t test partially and the coefficient of determination (R2) test. The results obtained in this study were e-service quality, website design, e-trust, and perceived risk together have a significant effect on e-satisfaction, e-service quality, website design, and e-trust partially have a positive and significant effect on e-satisfaction, while perceived risk has a negative and significant effect on e-satisfaction.